Blood, bones and body bits - Arnold, Nick; Arnold, Nick; De Saulles, Tony (London : Scholastic, 2008)
A series of comics are used to explore different functions of the human body.
Q
Title from case.
Contents indicated on side of case.
All volumes by Nick Arnold and illustrated by Tony De Saulles.
Each volume contains own index.
b
b
Keywords: Science -- Juvenile literature; Science -- Study and teaching (Primary)